Varnost mobilnih naprav - Markelj, Blaž; Bernik, Igor (University of Maribor Press, 2018)
Mobile device security. Globalization, accelerated rhythm of life and the urgency of quick decision making are factors that require unlimited access to information at any time and almost from everywhere. The rapid development of information technology by centralizing information systems, expanding wireless connections, accessing the Internet and developing mobile devices enables this. Technologies, of which high-performance mobile devices are very important, have spurred the development of various IT industries. The information revolution has transformed the world thoroughly, as well as previous steps on the path of technological development. Mobile devices, cyberspace, wireless networks with constant access and fast data transfer on the path of digital transformation have led to the complete tehnology dependence of individuals - at work in leisure and everyday life. The security of all mentioned elements is crucial.